Caracterización de la recuperación de medicamentos del sistema de distribución de medicamentos en dosis unitaria en el Hospital Víctor Lazarte Echegaray durante el año 2006 - Llapo Leiva, Denis Rafael (2008)
The Unit Dose Drug Distribution System (SMDUD) permits an adequate pharmacotherapeutic tracking in the patients, integration of the pharmacist to health’s team and it produces an important economic saving to the hospital. Our study it was orientated to describing the devolution percents produced for the SMDUD in the Víctor Lazarte Echegaray Hospital (VLEH) in the period 2006. Furthermore, identifying the causes of the devolution produced for the SMDUD. The method consisted in a retrospective-cross sectional analysis of the medical recipes. The results obtained showed that the devolutions summed up S/. 69 450.83. The therapeutic group of bigger recuperation was antibacterial with 40.81%. The principal types of errors were: overmedication 36.67%, medicaments in nursery room 16.82% and medicaments restricted 16.39%. The principal service of bigger recuperation was the medicine service with 30.19%. The results obtained showed the effectiveness of this method which become in savings to the hospital, decreasing the lost of money, deterioration, expiry date and others, recover the medications not administered to the patient and decreasing the errors of medications